Reactivity of Stabilized Li/Cl Carbenoids towards Lewis Base Adducts of BH3: BH Bond Activation versus Carbene Dimerization. Issue 36 (29th July 2013) - Molitor, Sebastian; Gessner, Viktoria H.
<x xml:space="preserve">Abstract</x> BH bond activation: Depending on the stability of the borane adduct, Li/Cl carbenoids react with BH3⋅LB either under BH bond activation at the carbenic carbon center or under carbene dimerization. The BH bond activation proceeds in a stepwise fashion with the nucleophilic attack of the Li/Cl carbenoid at BH3⋅LB as the crucial step determining the course of the reaction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>